Synthesis of phase-pure SnO2 nanosheets with different organized structures and their lithium storage properties - Chen, Jun Song (2013)
A facile hydrothermal method has been developed to synthesize phase-pure SnO2 nanosheets with controlled morphology. The electrochemical measurements show that the as-prepared sample exhibits improved lithium storage properties as an anode material for lithium-ion batteries.